Synthesis of Fluorescence Chemosensor Pb2+ and Cu2+ Ions from Pyrazoline Derivatives Compounds with Lanthanum (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2023)
Heavy metal ion pollutant waste Pb2+ and Cu2+ are getting attention due to the increasing amount, especially in various industrial field and transportation. The sensor of lanthanum (La) complexes with fluorescence-based pyrazoline derived has the potential to detect Pb2+ and Cu2+ heavy metal ions. The complex compounds were characterized by spectroscopic methode and stoichiometry of the La3+ pyrazoline complex was determined using the Job method. The determination of stoichiometric showed that 1 mole of lanthanum complex compounds can bind 10 moles of pyrazoline-derived ligands so that the predictable structure is bicapped square antiprism. The results of scanning the metal ion complex La3+ with pyrazoline-derived ligands using a UV-Vis spectrophotometer obtained three absorption peaks at 255 nm, 307 nm, and 359 nm with a molar absorptivity value (log ɛ) of respectively in 4.30; 4.25 and 4.13, three peaks are indicating the presence of a transition type π→π* and n→π*. The results of the fluorescence spectrophotometer showed two emission peaks, the absorption peak of the La3+ complex compound was in the 370 nm region with fluorescence intensity of 2925 a.u and a 470 nm region with a fluorescence intensity of 796.4 a.u. The determination of the fluorescence chemosensor (fluorosensor) potential of the La3+ complex compound with the addition of Pb2+ and Cu2+ metal ions showed a significant fluorescence change so that the fluorosensor type was obtained for the La3+ metal ion complex compound with Pb2+ and Cu2+, namely "turn-on" and "turn-off" respectively.